2017
DOI: 10.1016/j.jcsr.2017.01.013
|View full text |Cite
|
Sign up to set email alerts
|

Experimental and numerical investigation of novel partially connected steel plate shear walls

Abstract: A steel plate shear wall system, consisting of a thin steel plate connected to the boundary frame members, is proposed as lateral load resisting system for use in the multi-storey building. To reduce the potential damage on the boundary elements caused by the tension field action in the steel plate after buckling, the steel plate is partially connected at the corner edges to the boundary frame members by bolts. Two scaled specimens were tested under cyclic loads to investigate the hysteretic behaviour of the p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(14 citation statements)
references
References 10 publications
1
13
0
Order By: Relevance
“…Karp [22] exposes standard plane formulation of dynamic response of material orthotropic and frequency of excitation. Clayton et al [23] and Wei et al [24] also prove that external load effect only influences stress field distribution within a certain range by composite structure experiments. e best location of measuring devices based on well-known static data for composite structure according to Saint-Venant's principle is recommended twofold size of research area with appropriate boundary conditions.…”
Section: Specimen Preparationmentioning
confidence: 91%
“…Karp [22] exposes standard plane formulation of dynamic response of material orthotropic and frequency of excitation. Clayton et al [23] and Wei et al [24] also prove that external load effect only influences stress field distribution within a certain range by composite structure experiments. e best location of measuring devices based on well-known static data for composite structure according to Saint-Venant's principle is recommended twofold size of research area with appropriate boundary conditions.…”
Section: Specimen Preparationmentioning
confidence: 91%
“…Loading protocol of SAC (ASTM, American Society for Testing and Materials 2006) as is depicted in Figure 7 is used as displacement history in this study. Based on previous studies (Wei et al 2017b;Shekastehband, Azaraxsh, and Showkati 2018), the maximum lateral drift is set at 5%. FEMA 350 (FEMA-350 2000) for special moment-resisting frames (SMFs) suggests two drift angles corresponding to strength degradation and ultimate drift angles, which are 0.04 and 0.06, respectively.…”
Section: Loading Protocolmentioning
confidence: 99%
“…Reviewing experiments on unstiffened SPSW reveals that the aspect ratio of the web plays a dominant role in configuring its seismic performance. Figure 1 Wei et al 2017b, Behbahanifard 2003. As could be seen, for the increasing aspect ratio of the SPSW, there are substantial increases in the displacement ductility and maximum inter-story drift.…”
Section: Introductionmentioning
confidence: 99%
“…Ozcelik and Clayton [8] presented an equation that is proposed for partial tension field inclination angle of beam connected steel plate shear walls. Wei et al [9] stated that an inclination angle of approximately 45° was observed for partially connected steel plate shear walls.…”
Section: Introductionmentioning
confidence: 99%